Nutrient footprint as a tool to evaluate the nutrient balance of a food chain. (20th January 2016) - Grönman, Kaisa; Ypyä, Jenni; Virtanen, Yrjö; Kurppa, Sirpa; Soukka, Risto; Seuri, Pentti; Finér, Aki; Linnanen, Lassi
Abstract: The unsustainable use of nutrients such as nitrogen (N) and phosphorus (P) has resulted in the straining of the environment to excess. To improve this situation, a better knowledge of the nutrient flows is necessary. Even though nutrient balances and emissions have been calculated, an illustrative calculation method for the efficient use of nutrients use is still lacking. This article presents a novel methodology for a nutrient footprint, which takes into account 1) the amount of nutrients taken into use as virgin or recycled nutrients and 2) the efficiency of these nutrients utilized in that particular production chain. At the same time, nutrient losses at each life cycle phase are identified. Hence, the nutrient footprint is an indicator which combines the amount of captured nutrients [kg of N and P] for use in the production chain and the share of nutrients utilized [%] either in the product itself or in the entire production chain, accounting also for side-products. The nutrient footprint method is tested using oat flakes and porridge as a case product. The case calculation results reveal a relatively efficient use of the nutrients, as the nutrient use efficiency (NUE) of the production chain for N is 71% and for P 99%. When examining only the NUE of the oat flakes and porridge and excluding the side-products, the nutrient use efficiency is 55% for both N and P. The case calculation also reveals the hotspots for nutrient losses, which were located in the wastewater and food waste treatment. The nutrient footprint methodology seems to have potential in assessing the nutrient balances of food chains as well as other bio-based production chains. It offers information about the nutrient usage and utilization efficiency in a simple and comparable form. This information can not only be used in improving the production chains but also in communicating the importance of the sustainable use of nutrients to decision makers. Highlights: We propose a novel method for calculating a nutrient footprint. Combined indicator of the amount and use efficiency of virgin and recycled nutrients. Case calculation for oat flakes had a good nutrient use efficiency (NUE) overall. The hotspots in the case were in the waste treatment processes with low NUEs. Aim of the method is to improve the NUE of bio-based materials and energy chains.